Supplementation of Sakura Block Plus on Palm Frond-Based Rations on the Production Efficiency of Kaur Cattle - Jarmuji Jarmuji; Lili Warly; Mardiati Zain; Khasrad Khasrad (Universitas Bengkulu, 2023)
This study evaluates the effectiveness of fattening Kaur cattle-fed sakura block plus supplements and ammoniated palm frond-based rations. The production efficiency of Kaur cattle fed with sakura block plus supplements and ammoniated palm-frond-based ration. The study design uses Latin Square Design (LSD) with treatments P0 (10% sakura block plus), P1(12% sakura block plus), and P3 (14% sakura block plus). This study employed four 12-month-old male Kaur cattle for four 10-day treatment periods. Ration Efficiency (RE), Feed Cost per Gain (FC/G), Income Over Feed Cost (IOFC), and Revenue per Cost Ratio (R/C) were not substantially different between treatments (P>0.05).